2006
DOI: 10.1584/jpestics.g06-09
|View full text |Cite
|
Sign up to set email alerts
|

Properties and biological control activities of aerial and submerged spores in Trichoderma asperellum SKT-1

Abstract: Trichoderma asperellum SKT-1, a biocontrol agent that is highly effective against rice seedborne diseases, forms submerged spores by liquid culture. These submerged spores had some common properties with aerial spores, but differed in surface topology and internal organization. Aerial spores, so called conidia, maintained high viability under dry storage conditions, whereas the viability of submerged spores was reduced. The cell wall of submerged spores was thinner than that of aerial spores, and the surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…33) It is noteworthy that the optimum growth temperature (27°-30°C) of SKT-1 is almost the same as the optimum temperature for rice seed germination and seedling growth, suggesting that SKT-1 is an ideal biocontrol agent. 43) In our experiments, SEM observation showed direct mycoparasitic interaction between T. asperellum SKT-1 and G. fujikuroi on the seed surface, and degradation of the cell wall of G. fujikuroi by hyphae of SKT-1. Inbar et al (1996) 44) showed hyphae of T. harzianum strain BAFC Cult.…”
Section: Discussionsupporting
confidence: 58%
“…33) It is noteworthy that the optimum growth temperature (27°-30°C) of SKT-1 is almost the same as the optimum temperature for rice seed germination and seedling growth, suggesting that SKT-1 is an ideal biocontrol agent. 43) In our experiments, SEM observation showed direct mycoparasitic interaction between T. asperellum SKT-1 and G. fujikuroi on the seed surface, and degradation of the cell wall of G. fujikuroi by hyphae of SKT-1. Inbar et al (1996) 44) showed hyphae of T. harzianum strain BAFC Cult.…”
Section: Discussionsupporting
confidence: 58%
“…Propagules, like submerged spores, must retain a high level of viability under adverse and variable conditions, where the conidial mass of Trichoderma is the most proficient propagule, tolerating downstream processing . Moreover, reduction of the mycelia in the liquid culture, increasing the spore population, would also be desirable, since mycelia create separation and disposal problems …”
Section: Resultsmentioning
confidence: 99%
“…Compost made with agricultural waste and the Trichoderma asperellum strain suppresses Rhizoctonia solani in cucumber seedlings 3 . Trichoderma asperellum was reported as a potent bio control agent against seed-borne rice diseases in a previous study 4 . In our laboratory Trichoderma longibrachiatum was reported to be entomopathogenic against Leucinodes orbonalis , a major pest of eggplant 5 .…”
Section: Introductionmentioning
confidence: 97%